Fabrication of polyvinyl alcohol/chitosan oligosaccharide hydrogel: physicochemical characterizations and in vitro drug release study - Mahato K.K.; Sabbarwal S.; Misra N.; Kumar M. (My University, 2025)
Hydrogel composites from polyvinyl alcohol and chitosan have been developed by various researchers as a function of their composition for various medical applications. Although, the solubility of chitosan in acidic solvents may limit its wide bioengineering applications. In this article, we demonstrate that polyvinyl alcohol-chitosan oligosaccharide (water soluble) to develop cross-linked hydrogel network using chemical cross linker. X ray diffraction, Fourier transform infrared spectroscopy, and wettability study of these hydrogels were also performed. Lomefloxacin drug was loaded into the hydrogels and its release profile was studied. © 2020, © 2020 Taylor & Francis Group, LLC.